Pengaruh Jumlah Kunjungan Wisatawan dan Tingkat Hunian Hotel Terhadap Pendapatan Asli Daerah Dan PDRB Di Aceh - Puspa Sari Aceh, Adinda; Syahri Ramdhaniah, Anggun; Eka Safitri Sayuti, Ella; Asnidar, Asnidar (CV. Lafadz Jaya, 2022)
The purpose of this study was to determine the effect of the number of tourist visits and hotel occupancy rates on local revenue (PAD) and gross regional domestic product (GRDP).This type of research is descriptive quantitative.The type of data is secondary data.This study uses time series data,which uses 10 years of data from 2010-2019 in Aceh Province using a path analysis regression approach.The results of this study indicate that the number of tourist visits has a positive and significant effect on regional original income and gross regional domestic product, while the hotel occupancy rate does not have a positive effect on regional original income and gross regional domestic product. Local revenue has an insignificant positive effect on gross regional domestic product. With this, it is hoped that the government can encourage the development of the tourism sector in Aceh by paying attention to facilities and infrastructure, road access, or accommodation in tourist attractions.